The Role Of Government Public Relations In Building A Positive Image - Deswana Raya; Riski Apriliani (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Image is one of the crucial things needed by an organization, it determines how an organization is viewed by the public. However, the image of an organization does not automatically form. Therefore, it is necessary to have the role of a Public Relations. Good or bad image of an organization is determined by how a Public Relations builds an image, if the image is built in a good direction, it will certainly provide benefits. Conversely, if the image is built in a bad direction it will cause losses. The research was written with the aim of knowing the role of Public Relations in building the image of the Surakarta Customs and Excise Supervision and Service Office (KPPBC TMP B Surakarta), using qualitative methodology and data collection techniques, namely interviews, observations and literature studies. To test the validity of the data, this research uses a credibility test with triangulation techniques. In this research, Public Relations of the Surakarta Customs and Excise Supervision and Service Office (KPPBC TMP B Surakarta) is the subject of research. With this research, it is hoped that it can help the agency's Public Relations in building a positive image of the company to face the increasing number of negative news exposure that can reduce public trust in the agency.